The Relationship Between Mothers’ Knowledge about PHBS, Stunting, and Nutrition with Helminth Infection among Toddlers in Jember - Azyumardi Azra Kautsar; Yudha Nurdian; Irawan Fajar Kusuma; Ancah Caesarina Kusuma (KHD-Production, 2023)
Helminth infection are still a problem in the world. According to WHO, children aged 1-4 years have a high morbidity of helminthic infections. The number of Helminthinfections in children is influenced by several factors, one of which is PHBS (Clean and Healthy Living Behavior). In addition, children who are stunted or malnourished are prone to Helminthinfections. This can be prevented with the role of mother's knowledge regarding PHBS, stunting, and nutrition. This study aims to analyze the relationship between mother's knowledge about PHBS, stunting, and nutrition with Helminths in toddlers in Jelbuk District, Jember Regency. This research has a type of observational analytic research with a cross-sectional design. The population consists of mothers who have toddlers aged 12-59 months in Jelbuk District, Jember Regency. The sampling technique used consecutive sampling and obtained 69 mothers. Knowledge obtained from interviews using a questionnaire. Helminthinfections in toddlers are obtained from stool examination using flotation techniques. Data analysis using Mann Whitney. The results showed that there were 4 toddlers (5.7%) who had Helminth infections. 3 toddlers were infected with Ascaris lumbricoides (4.34%) and the rest were hookHelminths (1.44%). The majority of mothers have good knowledge on all indicators of knowledge of PHBS and nutrition, but lack of knowledge on stunting. Analysis using the Mann Whitney test showed that there was a relationship with Helminths only on 2 indicators of PHBS, namely smoking (Sig.(2-tailed)=0.036) and house cleanliness (Sig.(2-tailed)=0.027). The conclusion of this study is that there is a relationship between knowledge of house hygiene and smoking with Helminths in children under five and there is no relationship between knowledge of healthy latrines, clean water, garbage disposal, consumption of fruit vegetables, stunting, and nutrition..